The association of three vaccination doses with reduced gastrointestinal symptoms after severe acute respiratory syndrome coronavirus 2 infections in patients with inflammatory bowel disease - Hong, Yu; Che, Tianyi; Shen, Xiangguo; Chen, Jie; Wang, Kui; Zhao, Lingying; Gao, Weitong; Zhang, Yao; Ge, Wensong; Gu, Yubei; Zou, Duowu (Frontiers in Medicine, 2024)
The protective efficacy of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination against new-onset gastrointestinal (GI) symptoms following COVID-19 infection is critical among patients with inflammatory bowel disease (IBD); however, the optimal protective vaccine dosage remains unknown. Therefore, this study aimed to clarify whether there is a correlation between SARS-CoV-2 vaccinations and GI symptoms following Omicron infection in patients with IBD. We conducted a multicenter cross-sectional study of IBD patients among three tertiary hospitals in eastern China. Professional physicians collected all data using online questionnaires. The patients were stratified into four groups: unvaccinated and one, two, or three vaccination doses. The primary outcome was the presence of any new-onset GI symptoms after SARS-CoV-2 infection before a negative SARS-CoV-2 nucleic acid testing or a negative self-testing for antigens. In total, 536 patients with IBD (175 unvaccinated, 31 vaccinated, 166 vaccinated with two doses, and 164 vaccinated with three doses) reported having COVID-19 infection. Compared with the unvaccinated, the three vaccination doses group was associated with reduced GI symptoms after infection (adjusted odds ratio=0.56, 95% confidence interval 0.34-0.90, P<0.05). Reduced diarrhea (adjusted odds ratio=0.54, 95% confidence interval 0.31-0.92, P<0.05) and nausea or vomiting (adjusted odds ratio=0.45, 95% confidence interval 0.21-0.92, P<0.05) were observed in the three vaccination doses group compared with the unvaccinated group. In conclusion, in the 536 patients with IBD who reported COVID-19 infection, we found that the three vaccination doses, but not the one or two doses group, were associated with reduced GI symptoms after infection compared with the unvaccinated group.